Self-insight : roadblocks and detours on the path to knowing thyself - Dunning, David (David A.) (Essays in social psychology., 2005)
People base thousands of choices across a lifetime on the views they hold of their skill and moral character, yet a growing body of research in psychology shows that such self-views are often misguided or misinformed. Anyone who has dealt with others in the classroom, in the workplace, in the medical office, or on the therapist's couch has probably experienced people whose opinions of themselves depart from the objectively possible. This book outlines some of the common errors that people make when they evaluate themselves. It also describes the many psychological barriers - some tha.